2007
DOI: 10.1097/ico.0b013e318151f8e8
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin Glue for Opposing Wound Edges in “Top Hat” Penetrating Keratoplasty

Abstract: The use of fibrin glue in Top Hat PKP was found to be more mechanically stable than traditional sutures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…in 2007. [100,101] They reported that in “Top Hat” keratoplasty, fibrin glue was mechanically more stable than suturing. They used incisional bursting pressure of 185 mmHg (range 90-300 mm Hg) for testing stability, demonstrating that fibrin glue provides faster healing and induces significantly less corneal vascularization.…”
Section: Fibrin Glue In Ophthalmologymentioning
confidence: 99%
“…in 2007. [100,101] They reported that in “Top Hat” keratoplasty, fibrin glue was mechanically more stable than suturing. They used incisional bursting pressure of 185 mmHg (range 90-300 mm Hg) for testing stability, demonstrating that fibrin glue provides faster healing and induces significantly less corneal vascularization.…”
Section: Fibrin Glue In Ophthalmologymentioning
confidence: 99%
“…Los procedimientos quirúrgicos empleados fueron QPP tradicional, QPP tipo «top-hat» asistida por láser femtosegundos y queratoplastia «top-hat» con uso de adhesivo tisular; para los 3 procedimientos se utilizaron 8 y 16 suturas. En ambos casos, la técnica de «top-hat» combinada con adhesivo tisular demostró estadísticamente una mayor estabilidad de la herida comparada con los otros métodos, soportando presiones mayores de 146 y 158 mmHg para 8 y 16 suturas respectivamente; el astigmatismo inducido también fue menor que en los otros procedimientos, siendo de 2.5 D para la técnica con adhesivo vs. 3.1 D para las otras 2 técnicas 22 .…”
Section: Discussionunclassified
“…in 2007 in “top hat” keratoplasty and they found fibrin glue mechanically more stable than suturing. [10]…”
Section: Discussionmentioning
confidence: 99%